Carboboration of isocyanates with tris(pentafluorophenyl)borane and evidence for dissociative FLP chemistry of an acid–base pair. Issue 48 (29th May 2019) - Mehta, Meera; Goicoechea, Jose M.
Abstract : We describe carboelementation reactions involving tris(pentafluorophenyl)borane [B(C6 F5 )3 ] with isocyanates, and contrast this reactivity with that of the heavier group 13 Lewis acids Al(C6 F5 )3 and Ga(C6 F5 )3 . Abstract : We report on the reactivity of isocyanates towards tris(pentafluorophenyl)borane which was found to result in the 1, 2-carboboration of the isocyanate CO bond. The resulting six-membered heterocyclic compounds can be rationalized as adducts of imino-boranes with isocyanates and react accordingly, allowing for the dissociative displacement of the trapped isocyanate moiety in a series of exchange reactions. Related carboelementation reactions with the heavier group 13 analogues, Al(C6 F5 )3 and Ga(C6 F5 )3, result in a dimerization of the carboboration products to afford eight-membered heterocycles.